The interactive whiteboard and the development of dialogic interaction in the context of problem solving - Canavarro, Ana Paula (2019)
This paper focuses on the identification and analysis of the contributions that the interactive whiteboard can provide for the development of dialogical interaction in the context of problem-solving, by identifying the features of the board that can be used to support this interaction. The interactive whiteboard proved to be a very versatile tool. Its features support increased interaction even in lessons where students do not really manipulate the board by themselves or in lessons where they do not solve tasks for sharing their own solutions with the class. This study also showed that the interactive whiteboard is worth full in the context of a class discussion orchestrated by the teacher, in order to present new contents. This scenario can be very rich as a stimulus for the promotion of interactions among all participants – the interaction can be dialogic depending more of teacher intentions and actions than of the technological resource being used in classroom. But the interactive whiteboard is not a neutral device and brings many contributions to promote dialogic interaction. Of particular interest is its use in the collective discussion of problem solutions, where multimodality and interactivity are simultaneously stimulus and support for promoting student mathematical learning. The features concerning quality written records are valuable in any phase of the lesson, but its use facilitates teacher management of whole class, namely, in the management of lesson time.